Quantitative trait loci for field resistance to barley stripe rust derived from malting line 95SR316A. Issue 4 (27th May 2020) - Esvelt Klos, Kathy; Hayes, Patrick; del Blanco, Isabel Alicia; Chen, Xianming; Filichkin, Tanya; Helgerson, Laura; Fisk, Scott; Bregitzer, Phil
Abstract: Developing improved barley ( Hordeum vulgare L.) germplasm with resistance to barley stripe rust (BSR) has been a goal of several breeding programs since the introduction of this disease into the Americas. The USDA–ARS two‐rowed spring malting barley breeding line 95SR316A, while susceptible at the seedling stage, has field resistance to BSR. This study was conducted to identify markers useful for marker‐assisted selection for resistance to BSR. This line was used as a parent in two biparental mapping populations: 95SR316A × 'Lenetah' (susceptible), and 95SR316A × 'Grannelose Zwiezelige' (GZ; seedling resistance). Progeny were observed for response to BSR infection in the field at four location–years per population. Disease severity was taken as the percentage of leaf area infected. The 95SR316A × GZ (F5 –derived recombinant inbred line [RIL]) and 95SR316A × Lenetah (doubled haploid) populations were genotyped using Illumina's 50K barley array. Interval mapping revealed quantitative trait loci (QTL) in both populations on chromosome 2H (Qpsh.316A.2Ha) near the p‐terminal, with the allele derived from 95SR316A contributing to lower disease severity. In addition, the 95SR316A × GZ population was segregating for a QTL on chromosome 2H (Qpsh.316A.2Hb) at ∼35 cM with effects on BSR observed in two location years. The 95SR316A × Lenetah population was segregating for Qpsh.316A.7H at 94.04 cM on chromosome 7H with peak logarithm of the odds (LOD) scores of 25.81, 36.75, and 5.35 observed in Corvallis, OR, in 2018, Davis, CA, in 2018, and Mt. Vernon, WA, in 2018, respectively. The QTL on chromosomes 3H, 5H, and 6H were observed in only single location–years in the 95SR316A × Lenetah population.